From "Migrant" to "Citizen": Labor Market Integration of Former Live-In Caregivers in Canada. (August 2018) - Banerjee, Rupa; Kelly, Philip; Tungohan, Ethel; Cleto, Petronila; de Leon, Conely; Garcia, Mila; Luciano, Marco; Palmaria, Cynthia; Sorio, Chris
This study examines the impact of attaining permanent resident status on the employment integration of migrant caregivers in Canada. The authors use survey data from 631 caregivers who arrived as migrants under a temporary foreign worker program before transitioning to permanent residency, as well as data from 47 focus group discussions. The authors find that although most caregivers do switch out of caregiving work over time, they often remain within a few, lower-skilled occupations. Postsecondary education acquired before migration has no impact on occupational mobility. Caregivers' lack of financial stability and the stigmatization of their employment experience often constrain their labor market options; moreover, an emotional bond and sense of obligation toward employers often hinder their ability to move out into other occupations, even after receiving legal permanent resident status. From the empirical results, the authors provide theoretical insights into the complex relationship between immigration patterns and labor markets.